Crystal Chemistry and Physics of UCd 11 - Zaremba, Nazar; Witthaut, Kristian; Prots, Yurii; Krnel, Mitja; Burkhardt, Ulrich; Fisk, Zachary; Grin, Yuri; Svanidze, Eteri (Inorganic chemistry, 2022)
In the phase diagram U-Cd, only one compound has been identified so far─UCd (space group 3̅ ). Since the discovery of this material, the physical properties of UCd have attracted a considerable amount of attention. In particular, its complex magnetic phase diagram─as a result of tuning with magnetic field or pressure─is not well-understood. From a chemical perspective, a range of lattice parameter values have been reported, suggesting a possibility of a considerable homogeneity range, , UCd . In this work, we perform a simultaneous study of crystallographic features coupled with measurements of physical properties. This work sheds light on the delicate relationship between the intrinsic crystal chemistry and magnetic properties of UCd .